Pre-ictal heart rate variability alterations in focal onset seizures and response to vagus nerve stimulation. (March 2021) - Hödl, Stephanie; Olbert, Elisabeth; Mahringer, Christoph; Struhal, Walter; Carrette, Evelien; Meurs, Alfred; Gadeyne, Stefanie; Dauwe, Ine; Goossens, Lut; Raedt, Robrecht; Boon, Paul; Vonck, Kristl
Highlights: VNS non-responders are characterized by a sudden pre-ictal decrease in HRV. The central autonomic network of VNS non-responders seems to be unable to counteract pre-ictal imbalance and unable to be altered by VNS. Pre-ictal HRV could serve as an additional predictive parameter for VNS response. Abstract: Purpose: Vagus nerve stimulation (VNS) is an effective and well-known treatment for drug resistant epilepsy (DRE) patients since 1997, yet prediction of treatment response before implantation is subject of ongoing research. Neuroimaging and neurophysiological studies investigating the vagal afferent network in resting state documented that differences in between epilepsy patients were related to treatment response. This study investigated whether an event-related parameter, pre-ictal heart rate variability (HRV) is associated with response to VNS therapy. Methods: DRE patients underwent video-electroencephalography (EEG) recording before VNS implantation. HRV parameters (time, non-linear and frequency domain) were assessed for every seizure during two 10 min timeframes: baseline (60 min before seizure onset) and pre-ictal (10 min before seizure onset). Pre-ictal HRV parameter alterations were correlated with VNS response after one year of VNS therapy and seizure characteristics (temporal/extratemporal, left/right or bilateral). Results: 104 seizures from 22 patients were evaluated. Eleven patients were VNS responders with a seizure frequency reduction of ≥ 50 % after one year of VNS. In VNS responders no changes in HRV parameters were found while in VNS non-responders the time domain and non-linear HRV variables decreased significantly (p = 0.024, p = 0.005, p = 0.005) during the pre-ictal time frame. 10/11 VNS non-responders had a seizure lateralization to the left compared to 4/11 VNS responders. Conclusion: VNS non-responders were characterized by a significant decrease of pre-ictal HRV (time domain/non-linear variables) suggesting a sudden autonomic imbalance probably due to an impaired central autonomic function that makes it at the same time unlikely to respond to VNS.